Oral Antibiotics Are Effective for the Treatment of Hand Osteomyelitis in Children. (March 2020) - Kargel, Jennifer S.; Sammer, Douglas M.; Pezeshk, Ronnie A.; Cheng, Jonathan
Background: Acute osteomyelitis of the hand is common in the pediatric population. Treatment with intravenous antibiotics is expensive and is associated with catheter-site infection and thrombosis. The purpose of this study is to investigate the efficacy of managing osteomyelitis of the hand in children with oral antibiotics.Methods: A retrospective review of cases of acute osteomyelitis of the hand at a single pediatric institution over a 4.5-year period was performed. Demographic and clinical data were reviewed, and treatment courses and outcomes were analyzed.Results: In total, 21 patients with acute osteomyelitis of the hand were included in the study. Of the 21 patients, 17 were initiated on a 6-week course of oral antibiotics upon diagnosis. Thirteen were successfully treated with oral antibiotics alone, 3 required subsequent surgical debridement, and 3 required conversion to intravenous antibiotics. Of the 21 patients, 4 were treated with surgical debridement upon diagnosis due to gross purulent drainage and then initiated on a 6-week course of oral antibiotics. All patients who underwent debridement were treated successfully with postoperative oral antibiotics.Conclusions: Most cases of osteomyelitis of the hand in children can be treated with oral antibiotics, either as the primary treatment or as postoperative therapy. Surgical debridement is indicated when purulence is present at the time of initial diagnosis or if the infection progresses during treatment with oral antibiotics. The use of oral antibiotics for treating acute osteomyelitis of the hand in children may result in decreased cost and fewer catheter-associated complications.